ORACLE HCM CLOUD: A FRAMEWORK FOR MODERN TALENT ACQUISITION AND AI-DRIVEN RECRUITMENT PROCESSES - Rekha Kota (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the transformative impact of Oracle HCM Cloud on modern talent acquisition processes, focusing on integrating AI-driven recruitment tools and their effectiveness in addressing contemporary hiring challenges. The article analyzes implementation data from multiple organizations, revealing significant improvements in key recruitment metrics: a 23% reduction in cost-per-hire, a 30% decrease in time-to-fill positions, and 85% accuracy in AI-driven candidate matching. The article demonstrates how cloud-based recruitment solutions revolutionize traditional hiring practices through a mixed-method approach combining quantitative analysis and qualitative assessment. The findings indicate that Oracle HCM Cloud's intelligent candidate screening, automated workflow management, and predictive analytics capabilities have substantially enhanced recruiter productivity, with an average of 40% time savings reported. Furthermore, the platform's impact on diversity and inclusion initiatives shows a 15% improvement in bias reduction metrics. The article also addresses critical ethical considerations in AI-assisted recruitment and provides a framework for successful implementation across various industry sectors. These findings contribute to the growing knowledge of digital transformation in talent acquisition and offer practical insights for organizations seeking to modernize their recruitment processes.